Kabbalah in Italy, 1280-1510 : a survey - Idel, Moshe, 1947- (Yale University Press, 2011)
This survey of the history of Kabbalah in Italy represents a major contribution from one of the world's foremost Kabbalah scholars. Idel charts the ways that Kabbalistic thought and literature developed in Italy and how its unique geographical situation facilitated the arrival of both Spanish and Byzantine Kabbalah.